Aplikasi Pembelajaran Bahasa Jerman untuk Pemula - Ongels, Widya; Noertjahyana, Agustinus; Setiawan, Alexander (Jurnal Infra, 2016)
According to Deutsch Austauschdinst (DAAD), more than 101 million people in the world are speaking German and about 20 million people around the world is learning about it. In addition to studying the German language in school or language-courses, it can also be done easily without having to spend a lot of money, simply by using German language learning application based on Android. The application aims to provide knowledge of German language for beginners or at the basic level, Start Deutsch A1 for all ages.Features provided for learning German is equipped with learning materials menu, quizzes menu as excercises and competency test menu which is the simulation test of Start Deutsch A1. To see the development of user capabilities, quizzes are equipped with the assessment contained in the score menu and review answers at the end of each quiz.Based on testing results, this learning application can run well on devices with the Android operating system version 4.1 to 5.0.2, and so is the process of accessing databases on the web services. In addition, the testing is also done by giving questionnaires to 10 respondents to determine the satisfactionâs level. Based on questionnaires, 80% of respondents said they were satisfied with the whole package of applications.